2019
DOI: 10.3390/foods8080293
|View full text |Cite
|
Sign up to set email alerts
|

Headspace Volatile Evaluation of Carrot Samples—Comparison of GC/MS and AuNPs-hpDNA-Based E-Nose

Abstract: The performances of a quartz crystal microbalances (QCMs) based on an electronic nose (E-nose), modified with hairpin-DNA (hpDNA) for carrot aroma profiling has been evaluated. Solid phase micro-extraction (SPME) headspace sampling, combined with gas chromatography (GC), was used as a reference method. The changes in carrot aroma profiles stored at different temperatures (−18 °C, 4 °C, 25 °C, and 40 °C) were monitored during time up to 26 days. The principal component analysis of the data evidenced the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…The lifetime of these sensors depends on the sensitive element, the method of deposition on the surface of the sensor, and their use in terms of number of measures. Some authors such as Mascini et al [ 70 ] tested the stability of peptide-based sensors on different days of analysis, Wang et al [ 78 ] tested the stability of the sensors, based on MIPs, exposing them every 5 days to known concentrations of target gas up to a maximum of 30 days obtaining the same response, Gaggiotti et al [ 112 ] tested the reproducibility of the hpDNA-based sensor array using octanal as the target gas over three months. By these few examples we can affirm that gas sensors based on peptides, MIPs and DNA appear stable enough to be used for robust detection in the long-term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lifetime of these sensors depends on the sensitive element, the method of deposition on the surface of the sensor, and their use in terms of number of measures. Some authors such as Mascini et al [ 70 ] tested the stability of peptide-based sensors on different days of analysis, Wang et al [ 78 ] tested the stability of the sensors, based on MIPs, exposing them every 5 days to known concentrations of target gas up to a maximum of 30 days obtaining the same response, Gaggiotti et al [ 112 ] tested the reproducibility of the hpDNA-based sensor array using octanal as the target gas over three months. By these few examples we can affirm that gas sensors based on peptides, MIPs and DNA appear stable enough to be used for robust detection in the long-term.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only two applications on real samples have been reported for DNA-based GSs in carrot and hemp samples. The same sensor array developed in [ 110 ] was used by Gaggiotti et al [ 112 ] to monitor volatiles profile change in carrots. A single batch of fresh carrots was blanched to inactivate enzymes and stored at different temperatures for 26 days.…”
Section: Peptides Dna and Mips As Sensing Elementsmentioning
confidence: 99%
“…Recently, Mascini et al [66] reported the use of hairpin DNA screened in silico against different chemical classes of VOCs. Their use on QCM and surface plasmon resonance (SPR) imaging chips was successful for gas sensing [67].…”
Section: Virtual Screeningmentioning
confidence: 99%
“…Furthermore, seven VOCs representing the aroma of carrots could well be discriminated. The volatile profile in real carrot samples detected with the sensor array was similar to the profile obtained with GC-MS. Changes in the aroma profiles of the samples resulting from different storage times and temperatures could be detected by the array [29,143].…”
Section: Qcm Multi-sensor Arraysmentioning
confidence: 99%